EFEKTIVITAS TEPUNG BUNGA KECOMBRANG (Nicolaia Speciosa Horan) SEBAGAI PENGAWET TERHADAP ASPEK KIMIA DAGING AYAM BROILER - Aji Windiyartono; Rr. Riyanti; Veronica Wanniatie (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The purpose of this study was to determine the effect of kecombrang flower powder as a preservative on chemical aspects of broiler meat.  This research was conducted in the Laboratory of Animal Production and Animal Nutrition Laboratory of the Department of Animal Husbandry, Faculty of Agriculture, University of Lampung.  Treatment using a completely randomized design (CRD) with four treatments and five replications.  The treatment consisted of concentration powder of kecombrang flower 0%, 2 %, 4 % and 6%.  BNT test showed significant effet (P <0.05) on water content, and no significant effect (P >0.05) on the protein and fat content of broiler meat. (Keywords: Kecombrang flowers, moisture content, fat content, protein content).